Mechanisms of Pathogenesis in Drug Hepatotoxicity Putting the Stress on Mitochondria - Jones, Dean P. (American Society for Pharmacology and Experimental Therapeutics, 2010)
Mitochondria play key roles in aerobic life and in cell death. Thus, interference of normal mitochondrial function impairs cellular energy and lipid metabolism and leads to the unleashing of mediators of cell death. The role of mitochondria in cell death due to drug hepatotoxicity has been receiving renewed attention and it is therefore timely to assess the current status of this area.